Associations between Fetal Symptoms during Pregnancy and Neonatal Clinical Complications with Toxoplasmosis - Nándor Tűzkő; Virág Bartek; Atene Simonyi; Ágnes Harmath; István Szabó; Dezso Peter Virok; Artur Beke (MDPI AG, 2024)
Introduction: Toxoplasmosis is a parasitism transmitted by Toxoplasma gondii, part of the TORCH complex, the most prevalent parasitism worldwide. It is asymptomatic in immunocompetent individuals but causes severe infections and developmental abnormalities in pregnant women, mainly affecting the central nervous system and the gastrointestinal system. Methods: In our prospective study, we analyzed cases of recent maternal Toxoplasma infections confirmed by serological testing between 1996 and 2020 at the Department of Obstetrics and Gynecology, Semmelweis University. Amniocentesis, followed by PCR, was performed in cases of recent infection confirmed by serological testing during pregnancy. After birth, a neonatological, microbiological, pediatric neurological and ophthalmological examination and a follow-up was carried out. Results: During the study period, a total of 238 cases of amniotic fluid Toxoplasma PCR testing due to Toxoplasma recent infection were performed. In terms of pregnancies, there were 219 deliveries and seven abortions. Twelve cases had no data available on the outcome of the pregnancy. In total, 133 cases of ultrasound abnormalities were detected during pregnancy, while in 105 cases, no abnormalities were detected on ultrasound examination. During amniocentesis, eight cases of Toxoplasma infection were revealed in amniotic fluid samples by PCR, and in 230 cases, the result was negative. Neonatal follow-up was performed in 139 cases, with no abnormalities during follow-up in 117 cases, and in 22 cases, there was a detectable complication that was likely to be related to Toxoplasma infection. In all 22 cases, amniotic fluid PCR Toxoplasma testing was negative. Conclusions: The most common ultrasound abnormalities involve the nervous system and the gastrointestinal system. In cases of suspicion, it is recommended to perform amniocentesis Toxoplasma PCR testing besides the indirect methods to help the pregnant woman decide whether to carry the pregnancy to term. During follow-up, a multidisciplinary team experienced in pregnancies complicated by toxoplasmosis must carry out the follow-up, care and subsequent development.